Revitalizing the Indonesian Language as a National Identity in the Globalization Era: Challenges and Strategies - Suhendi, Enjang Tatang (Journal of English Language and Education, 2025)
The use of Indonesian in public spaces is an important issue in maintaining national identity in the era of globalization. This study aims to explore the role of the use of Indonesian in public spaces in increasing public awareness of national identity and language revitalization strategies. This type of research is qualitative with a case study approach. The populations in this study were people living in the city of Bandung. The sampling technique used was purposive sampling with a sample size of 60 respondents, consisting of media actors, educators, and the general public. This study was conducted for six months, from January to June 2024. The results of the study show that although awareness of the importance of using Indonesian is high, there is inequality in the implementation of language policies in public spaces. The use of foreign languages, especially among the younger generation, affects the effectiveness of Indonesian revitalization. Therefore, a more holistic approach is needed in language revitalization, which involves public policy, culture-based education, and the use of digital technology. The implications of this study indicate the importance of strengthening more consistent language policies and integrating technology in learning Indonesian for the younger generation.